251 PREVALENCE AND CHARACTERISTICS OF SWALLOWING/COMMUNICATION IMPAIRMENTS IN FRAIL OLDER ADULTS ATTENDING THE EMERGENCY DEPARTMENT: A RETROSPECTIVE COHORT STUDY. (25th October 2022) - Boyle, O; Kelly, L; Whelan, C; Murtagh, E; O'Dwyer, A; Ryan, M; Hill, F; McCabe, A; Hayden, D
Abstract: Background: The presentation of frail older adults to the Emergency Department (ED) may be complicated by swallowing and/or communication impairment. Adults with communication impairment may experience difficulty accessing healthcare. Dysphagia is associated with frailty irrespective of age and/or number of chronic diseases [1]. This study aims to determine the prevalence and characteristics of swallowing and/or communication impairments among frail older adults attending the ED. Methods: A retrospective cohort study of consecutive ED attendees aged ≥ 75 years assessed by an interdisciplinary Gerontological ED team between October 2021 – February 2022 was conducted. A swallow/communication screening tool determined requirement for Speech and Language Therapy (SLT) referral. Data related to demographics and SLT interventions was extracted. Data analysis was completed using STATA Version 12. Ethical approval was obtained. Results: Among 518 patients, 118 (23%) (mean age 82.4 (+/-6.4) years, 54% male) required SLT assessment. These patients had high rates of frailty (Median CFS= 6 (IQR 5-7), suspected delirium (4AT ≥ 4 in 45%), suspected malnutrition (MNA score 0-11 in 75%), and probable sarcopenia (SARC-F= ≥ 4 in 75%). Therapy Outcome Measurement Scales and the Functional Oral Intake Scale were used in this first episode of SLT care. Oropharyngeal dysphagia was identified for 43% (27% mild, 10% moderate, 3% moderate-severe, 3% severe), with 6% presenting with signs/symptoms of oesophageal dysphagia. Changes in baseline communication was identified for 57%; cognitive communication difficulties (38%), dysarthria (11%), dysphonia (8%). SLT intervention and management approaches were initiated in the ED. Conclusion: Findings indicate a high prevalence of swallowing/communication impairment in frail older adults attending the ED. Future research should explore SLT outcomes at point of discharge to refine these swallowing/communication presentations. Reference: 1. Bahat G et al. Association between dysphagia and frailty in community-dwelling older adults. The Journal of Nutrition, Health & Ageing . 2019:23, 571–577.